Mereology in Kalām: A New Reading of the Proof from Accidents for Creation - Shihadeh, Ayman (Oriens, 2020)
Abstract The objective of this article is twofold. First, it investigates mereology in medieval Islamic theology, particularly the theologians’ claim that the whole is identical to its parts and accordingly that at least some attributes common to the parts must by extension be attributed of the whole. This claim was refuted by philosophers and, from the eleventh century onwards, an increasing number of theologians. Second, it offers a new interpretation of the standard theological proof from accidents for creation ex nihilo, to which this problem was central. A wide range of early, classical and later theological and philosophical sources are consulted.